P Wave Duration and P Wave Dispersion in Electrocardiography of Stroke Patients - Davutoğlu, Rale; Bedir, Ömer; Doğan, Sait Mesut (Harran Üniversitesi Tıp Fakültesi Dergisi, 2025)
Background: P-wave duration and P-wave dispersion (PWD) are electrocardiographic (ECG) markers of atrial conduction. This study aimed to compare these parameters in ischemic and hemorrhagic stroke patients versus controls and to examine the effects of stroke subtypes on atrial electrophysio-logy. Materials and Methods: This cross-sectional study included , 34 patients with ischemic stroke, 33 patients with hemorrhagic stroke, and 45 healthy subjects as control group. The 12-lead ECGs of all individuals taken at the time of admission to the hospital were analyzed. Maximum P wave duration (Pmax) and PWD were manually measured. All patients underwent brain CT and/or MRI within the first 24-48 hours of presentation, while echocardiography was performed within the first 48-72 hours of hospitalization. Results: Both stroke groups had significantly increased Pmax (ischemic: 130.3±11.9 ms, hemorrhagic: 118.8±14.7 ms, control: 91.8±11.5 ms; p<0.001) and PWD (ischemic: 40.9±13.3 ms, hemorrhagic: 43.6±13.1 ms, control: 23.8±9.1 ms; p<0.001) values compared to controls. No significant differ-ences were found between the ischemic and hemorrhagic groups. Conclusions: Ischemic and hemorrhagic stroke patients had prolonged P wave duration and increa-sed PWD during the acute phase of stroke compared to the control group. These findings suggest altered atrial conduction in stroke patients, regardless of stroke subtype, and may indicate an incre-ased risk of atrial fibrillation (AF) in this population.